Enhancing Digital Branding and Utilization of Meatball Printing Machines for MSMEs in Kampung Pentol, Surabaya - Desipradani, Gita; Fais, Ali; Mochklas , Mochamad; Ali, Moh; Lihabi, Lihabi; Irmawanto, Rudi; Pranugraha, Aftha Ferdian (SPEKTA (Jurnal Pengabdian Kepada Masyarakat : Teknologi dan Aplikasi), 2024)
Background: Kampung Pentol, an MSME in Sidotopo, Surabaya, led by Mrs. Irma Wulandari since 2022, faces challenges with manual production, traditional marketing, and halal certification. Solutions include a Meatball Printing Machine, digital branding, and halal certification to enhance competitiveness and market reach. Contribution: This initiative addresses key challenges in production, marketing, and halal certification, enhancing Kampung Pentol's capacity, competitiveness, and market expansion through targeted support and mentorship. Method: Activities include preparation, implementation, evaluation, and a sustainability plan to ensure ongoing development. Results: Outcomes include increased production via the Meatball Printing Machine, digital marketing adoption, and halal certification, expanding market reach and competitiveness. Conclusion: Modern tools, digital marketing, and halal certification enhanced Kampung Pentol's production, market reach, and business sustainability